IMPLEMENTASI PENILAIAN AUTENTIK DALAM PEMBELAJARAN DI SEKOLAH DASAR - Ade Suhendra (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2021)
AbstractThis paper describes the implementation of authentic assessment in learning in primary education which covers the basic concept of authentic assessment, the characteristics of authentic assessment, the technique of authentic assessment, and the benefits of authentic assessment. authentic assessment implemented to get real, original, valid, and reliable information. By obtaining this real, original, valid and reliable information, learning can be done well. Keywords: Implementation, Authentic assessment, Learning, Primary Education